FINANCIAL PERFORMANCE BY INSTITUTIONAL OWNERSHIP, EARLY WARNING SYSTEM (EWS), AND RISK BASED CAPITAL (RBC) (Case in Insurance Companies Listed on The Indonesia Stock Exchange, 2018-2021) - Muhamad Muslih; Prima Insan Kumala (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
A company's financial performance, which measures its level of soundness through time, is an accomplishment that can be made. High financial success reflects a company's strong reputation and might inspire investors to make an investment. Corporate governance processes and financial analysis play a significant role in managerial performance. It can be used to determine the financial strengths and weaknesses of an organization. For this reason, the purpose of  this study is to know the effect of institutional ownership, the Early Warning System (EWS), which is measured by the liquidity ratio, the claims expense ratio, and the premium growth ratio, and Risk Based capital (RBC) on financial performance that proxied by Return on Equity (ROE) for insurance sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2018–2021. Using the purposive sampling method, 15 samples were gathered. With Eviews 12, data analysis methods such as descriptive statistical analysis, the traditional assumption test, and panel data regression analysis were used in this study. The findings demonstrated that institutional ownership, the Early Warning System (EWS), and Risk Based Capital (RBC) all had an impact on company’s financial performance simultaneously. The claim expense ratio has a negative significant impact on company’s financial performance. Aside from institutional ownership, Risk Based Capital (RBC), premium growth ratios, and liquidity ratios have no impact on financial performance.